Mechanism of photoinduced luminescence degradation in CdSxSe₁₋x quantum dots - Kunets, V.P.; Kulish, N.R.; Lisitsa, M.P.; Bryksa, V.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
A possible mechanism of the photoinduced luminescence degradation in the hexagonal CdSxSe₁₋x quantum dots synthesized in a glass matrix is discussed using luminescence decay kinetic investigations and ab initio calculations of chemical bond energies at the boundary between CdSe cluster and SiOx fragment. The mechanism implies that the photoinduced break of Se-O bonds increases the electric field inside a quantum dot, which stimulates diffusion of the cadmium vacancy to the surface. This mechanism enables to explain the luminescence photodarkening effect in quantum dots as well as the degradation of the nonlinear optical device parameters.